Digital heart attack. (Economist, 2014)
The article discusses the Heartbleed bug software flaw that was discovered in the OpenSSL encryption software program and revealed on April 7, 2014 by researchers from the security firm Codenomicon Ltd., reporting that the bug could allow computer hackers to steal information from websites. Potential implications for businesses and consumers are described.